THREE “SRIKANDI” CANDIDATES IN THE 2024 EAST JAVA GUBERNATORIAL ELECTION: MEDIA FRAMING AND THE FUTURE OF WOMEN’S POLITICAL ROLES IN INDONESIA - Sujoko, Anang; Prasetyo, Bambang Dwi; Rosyidah, Ainun (CosmoGov: Jurnal Ilmu Pemerintahan, 2025)
This research aims to reveal the media imaging in framing the Three Srikandi Candidates for East Java Governor in 2024 with three stages of analysis, namely transitivity, assessment, and visual. At the same time, based on the analyses that have been conducted, this article also aims to assess the future of women's political roles in Indonesia. This article uses a multimodal discourse analysis method with a qualitative approach. The results showed that the media recognized the leadership capacity of the three women candidates for the 2024 East Java Governor. First, transitivity analysis in the news about the 2024 East Java governor election shows three female candidates as key actors in political contestation. Second, appraisal analysis shows that positive attitudes dominate, highlighting the competence and courage of the candidates. However, some perspectives also reveal the challenges faced by women, such as cultural stigma and double burden. Third, Visual analysis in the news reinforces the image of candidates through images that highlight personal and professional characteristics, thus creating closeness with the audience. For this reason, the media needs to take proactive steps in building a fairer narrative by minimizing stereotypes and focusing on women's professional achievements. By doing so, the media can contribute to a more equal and inclusive political future for women in Indonesia.gb777